Critical Control Point (CCP) on Freezing Hairtail Fish (Trichiurus savala) in PT Pan Putra Samudra, Rembang, Central Java - Muhammad Dzaky; Eka Saputra (Journal of Marine and Coastal Science, 2022)
Hairtail fish (Trichiurus savala) is potential to have a rapid deterioration due to the high water and protein content in the body of the fish. One of the efforts to prevent or slow down the deterioration of layur fish is by freezing treatment. The freezing process also cannot be completely avoided from the emergence of potential hazards, therefore a way to prevent or suppress potential hazards is needed by applying the Critical Control Point (CCP). The descriptive method with data collection including primary and secondary data was used in this study. The freezing process of layur fish at PT Pan Putra Samudra starts from receiving, sorting, weighting, labelling, washing, wrapping with plastic and arranging in cartons, freezing, packaging, and frozen storage. The stages determined as CCP in the freezing of layur fish are in the sorting stage. At the sorting stage, quality checking is performed including organoleptic and microbiological tests. It also checks physical hazards such as hooks and nets. The sorting stage is determined as CCP because in the next stage it cannot prevent or reduce the potential danger that exists in fish. Fish that have gone through quality checking and exceeding the threshold will be put in a special fish reject basket.